The Perception of Mental Health Issues That Affect Workplace Productivity in Klang Valley, Malaysia - Law, Kyra Ley Sy; Tiah, Benjamin Joo Wei (International Business Education Journal, 2022)
The businesses have been converging on ways to enhance their employees’ productivity and motivations for their shaken productivity. With this knowledge, businesses conduct various types of research to find solutions to improve employee’s productivity. The purpose of this research is to investigate the relationship between mental health status and employee’s productivity. The primary data was collected by using a quantitative approach among working individuals in Klang Valley, Malaysia. A total of 161 respondents in Klang Valley was gathered, and the results show that depression and anxiety disorder have a significant relationship with employees’ workplace productivity, whereas job stress and post-traumatic stress disorder do not have a significant relationship with employees’ workplace productivity. This research also found out that anxiety disorder is the most significant variable that affects employees’ workplace productivity. Mental health issues are currently arising and hardly acknowledged by organisation; thus, the results of this research focussed on the field of mental health issue affecting employee’s productivity.